Pengetahuan dan Kesiapan Mahasiswa Profesi Ners dalam Penerapan Evidence Based In Nursing pada Stase Keperawatan Maternitas dan Pediatrik - Selly Kresna Dewi; Margareta Martini; Sapariah Anggraini (Jurnal Sehat Mandiri, 2024)
Nursing is an integral part of health services, so professional services are the final product of nursing care. The application of Evidence Based Practice in nursing care helps answer the needs and challenges of professional nurses in developing their independent care. Nursing professional students are change agents in the world of nursing to be able to change care for the better so that services become more optimal. The basis for implementing EBP is the education they had during academics, so this research aims to see a picture of students' knowledge and readiness in implementing EBPN at the maternity and pediatric stages. This research is quantitative descriptive, with a total sampling of 30 respondents, and has passed an ethical review and uses a knowledge and readiness questionnaire. The data analysis used is Univariate and the results of this research state that students' knowledge is still lacking (70%) and their readiness is still lacking (53.3% ). The Evidence Based Practice in Nursing course at the undergraduate nursing education level is very necessary to increase students' knowledge and readiness to become change agents, so in this course there are more tricks to make it easier for students to learn EBPN more easily and there are internal workshops for institutions to strengthen independent intervention nurses based on EBPN.